Increased acid sphingomyelinase levels in saliva as oral mucositis severity predictors - Ordonez, Elsa Beatriz Monroy; Sprave, Tanja; Thomsen, Andreas R.; Schäfer, Henning; Grosu, Anca-Ligia; Jendrossek, Verena; Henke, Michael; Unger, Kristian; Klein, Diana (Frontiers in Oncology, 2025)
IntroductionRadiotherapy (RT) plays a central role in multidisciplinary treatment approaches in cancer therapy, particularly as an effective primary treatment modality for patients with head and neck cancer (HNC). One of the most common acute complications of RT for HNC patients is radiation-induced oral mucositis (OM), which can lead to severe oropharyngeal pain, swallowing and speech difficulties, and weight loss, thereby eventually causing interruption of RT. Although OM varies with tumor location and treatment methods, it is overall a common occurrence. However, it is unclear in which patients suffer from this severe condition. This study aimed to evaluate the suitability of acid sphingomyelinase (ASM) as a potential biomarker for predicting the risk of OM and to investigate the association with OM severity.MethodsWe investigated two independent patient cohorts from consecutive prospective studies (n=187). ASM protein levels were analyzed using Western blot analysis in unstimulated saliva samples collected from respective patients at least three days before the RT started. Patients were stratified according to OM occurrence and severity. Group comparisons were performed using non-parametric tests, while logistic regression was applied to assess associations between ASM levels and early OM development. Kaplan-Meier and Cox regression analyses evaluated correlations with overall and recurrence-free survival.ResultsIn the first cohort, 74 out of 109 patients developed OM during RT, and 42 displayed early OM at low radiation dose. Grade 3 OM developed in 50 (67.6%) patients after definitive and 24 (32.4%) after adjuvant RT. Thirty-four patients did not develop OM. A significant increase in ASM levels was detected in the saliva of patients who developed OM early. Respective findings were confirmed in a second cohort (n=78). 44 out of 78 patients developed OM, of which 21 patients displayed early OM. Fifty-three patients did not develop OM. Elevated ASM levels were confirmed in the saliva of patients who developed OM early, an observation that was found particularly in the saliva of HPV-negative patients. HPV-positivity was present in 32 (41,0%) patients. Overall, regression-free survival did not correlate with the incidence of OM or HPV status.ConclusionAlthough there is currently limited evidence for the potential implementation of salivary biomarkers to assess their association with the severity of OM, the findings here show that determining ASM levels in the saliva of HNC patients before starting RT could be a promising method to predict OM risk.